Effectiveness of a Mobile App (KhunLook) Versus the Maternal and Child Health Handbook on Thai Parents' Health Literacy, Accuracy of Health Assessments, and Convenience of Use: Randomized Controlled Trial - Rosawan Areemit; Suchaorn Saengnipanthkul; Sumitr Sutra; Pagakrong Lumbiganon; Phenphitcha Pornprasitsakul; Pongsatorn Paopongsawan; Kunwadee Sripanidkulchai (JMIR Publications, 2023)
BackgroundChildren of parents who have higher health literacy (HL) benefit more from preventive child health care. Digital interventions have been used to improve parents' HL with high satisfaction. KhunLook is a Thai mobile app conceived using strategies to improve HL. It was developed to assist parents in assessing and keeping track of their child's health in complement to the standard Maternal and Child Health Handbook (MCHH). ObjectiveThis trial focuses on the effectiveness of using the KhunLook app with the MCHH and standard care (intervention) compared with the conventional MCHH and standard care (control) on parents' HL. Data on accuracy of parents' assessment of their child's health and growth as well as convenience of use of the tool (app or MCHH) in the well-child clinic were collected at 2 visits (immediate=visit 1, and intermediate=visit 2). MethodsParents of children under 3 years of age who (1) had a smartphone or tablet and the MCHH and (2) could participate in 2 visits, 2-6 months apart at Srinagarind Hospital, Khon Kaen, Thailand, were enrolled in this 2-arm parallel randomized controlled trial between April 2020 and May 2021. Parents were randomized 1:1 to 2 groups. At visit 1, data on demographics and baseline HL (Thailand Health Literacy Scales) were collected. Parents in the app group used the KhunLook app and the control group used their child's handbook to assess their child's growth, development, nutrition and feeding, immunization status and rated the convenience of the tool they used. At visit 2, they repeated the assessments and completed the HL questionnaire. ResultsA total of 358 parents completed the study (358/408, 87.7%). After the intervention, the number of parents with high total HL significantly increased from 94/182 (51.6%) to 109/182 (59.9%; 15/182; Δ 8.2%; P=.04), specifically in the health management (30/182; Δ 16.4%; P<.001) and child health management (18/182; Δ 9.9%; P=.01) domains in the app group, but not in the control group. Parents in the app group could correctly assess their child's head circumference (172/182, 94.5% vs 124/176, 70.5%; P<.001) and development (173/182, 95.1% vs 139/176, 79.0%; P<.001) better than those in the control group at both visits. A higher proportion of parents in the app group rated their tool as very easy or easy to use (174-181/182, 95.6%-99.5% vs 141-166/176, 80.1%-94.3%; P<.001) on every item since the first visit. ConclusionsOur results suggest the potential of a smartphone app (KhunLook) to improve parents' HL as well as to promote superior accuracy of parents' assessment of their child's head circumference and development, with a similar effect on weight, height, nutrition and feeding, and immunization as in traditional interventions. Using the KhunLook app is useful and more convenient for parents in promoting a healthy child preventive care during early childhood. Trial RegistrationThai Clinical Trials Registry TCTR20200312003; https://www.thaiclinicaltrials.org/show/TCTR20200312003